2012
DOI: 10.1057/ces.2012.15
|View full text |Cite
|
Sign up to set email alerts
|

This Time It's Different? Youth Labour Markets during ‘The Great Recession’

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(78 citation statements)
references
References 22 publications
1
71
0
6
Order By: Relevance
“…Differentials in the employment rates of males and females should be reflected in WLE, but might have decreased, as the gap between male and female unemployment rates appears to have closed, at least during the beginning of the recession (e.g., O'Higgins 2011). Moreover, losses in WLE due to the crisis might be more concentrated at younger ages (Dudel et al 2018;O'Higgins 2012). We can also expect to observe regional differences in WLE both before and during the crisis, with the changes in WLE being especially large in the South, which has been more affected by the crisis than the rest of the country (Lagravinese 2015).…”
Section: The Italian Contextmentioning
confidence: 99%
“…Differentials in the employment rates of males and females should be reflected in WLE, but might have decreased, as the gap between male and female unemployment rates appears to have closed, at least during the beginning of the recession (e.g., O'Higgins 2011). Moreover, losses in WLE due to the crisis might be more concentrated at younger ages (Dudel et al 2018;O'Higgins 2012). We can also expect to observe regional differences in WLE both before and during the crisis, with the changes in WLE being especially large in the South, which has been more affected by the crisis than the rest of the country (Lagravinese 2015).…”
Section: The Italian Contextmentioning
confidence: 99%
“…Studies done by Scarpetta, Sonnet and Manfredi, (2010), O'Higgins, (2012) ;Brada, Marelli and Signorelli, (2014) revealed the implication of long-run consequences of unemployment on youth. They found that unemployment led to loss of work experience, reduce earnings for the entire life and poor job quality.…”
Section: Responsibility Of the Conference Organization Committeementioning
confidence: 99%
“…However, studies investigating the impact of the crisis on youth labor market performance are still scarce (Choudhry et al, 2012a, b), especially as regards the risk of creating a 'lost generation' due to the current crisis (Scarpetta et al, 2010). In this issue, O'Higgins (2012) analyzes the effects of the Great Recession on young people's labor market experiences in the European countries during the period 2008-2011, taking into account the role of different labor market institutions.…”
Section: Segmentations and Mismatchesmentioning
confidence: 99%